An analysis of euro area sovereign CDS and their relation with government bonds - Alessandro Fontana; Martin Scheicher (European Central Bank (ECB), 2010)
This paper studies the relative pricing of euro area sovereign CDS and the underlying government bonds. Our sample comprises weekly CDS and bond spreads of ten euro area countries for the period from January 2006 to June 2010. We first compare the determinants of CDS spreads and bond spreads and test how the crisis has affected market pricing. Then we analyse the `basis' between CDS spreads and bond spreads and which factors drive pricing differences between the two markets. Our first main finding is that the recent repricing of sovereign credit risk in the CDS market seems mostly due to common factors. Second, since September 2008, CDS spreads have on average exceeded bond spreads, which may have been due to `flight to liquidity' effects and limits to arbitrage. Third, since September 2008, market integration for bonds and CDS varies across countries: In half of the sample countries, price discovery takes place in the CDS market and in the other half, price discovery is observed in the bond market.
Keywords: G00; G01; 330; CDS; Credit Spread; financial crisis; Government bond; limits to arbitrage; Kreditderivat; Kreditversicherung; Öffentliche Anleihe; Kreditrisiko; Finanzkrise; Eurozone; EU-Staaten